Perspectives on the Limitations and Challenges of Standardized Testing in Education - Obiageli Okafor, Josephine (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Abstract Standardized testing remains a pivotal tool for assessing educational outcomes, yet it has been subject to widespread critique for its limitations and challenges. The present study presents perspectives on the limitations and challenges of standardized testing in education. A quantitative approach was employed using a survey questionnaire to gather data from 75 educators, including teachers and administrators from tertiary institutions in Anambra State, Nigeria. The questionnaire was trial-tested and validated, with a Cronbach's alpha coefficient of 0.89, ensuring reliability. Data were collected via an online survey using Google Forms, and the responses were analyzed using descriptive statistics. Findings reveal that educators face multiple challenges, including time constraints, lack of professional development, and pressure from administrators to meet test score targets. Additionally, standardized tests were found to limit innovative teaching methods and fail to adequately assess students' creativity, problem-solving abilities, and long-term learning. These results highlight the significant impact standardized testing has on teaching practices and the educational system as a whole. The study concludes by emphasizing the need for a more holistic approach to student assessment and suggests the adoption of alternative evaluation methods to address these challenges